MRI-guided focal or integrated boost high dose rate brachytherapy for recurrent prostate cancer - Ménard, Cynthia; Navarro-Domenech, Inmaculada; Liu, Zhihu (Amy); Joseph, Lisa; Barkati, Maroie; Berlin, Alejandro; Delouya, Guila; Taussky, Daniel; Beauchemin, Marie-Claude; Nicolas, Benedicte; Kadoury, Samuel; Rink, Alexandra; et al. (Frontiers in Oncology, 2022)
Background and Purpose: Locally recurrent prostate cancer after radiotherapy merits an effective salvage strategy that mitigates the risk of adverse events. We report outcomes of a cohort enrolled across two institutions investigating MRI-guided tumor-targeted salvage high dose rate brachytherapy (HDR-BT). Materials and Methods: Analysis of a prospective cohort of 88 patients treated across two institutions with MRI-guided salvage HDR-BT to visible local recurrence after prior radiotherapy (RT). Tumor target dose ranged from 22-26 Gy, using either an integrated boost (ibBT) or focal technique (fBT), delivered in two implants over a median of 7 days. Outcome metrics included cancer control and toxicity (CTCAE). Quality of life (QoL-EPIC) was analyzed in a subset. Results: At a median follow-up of 35 months (6 -134), 3 and 5-year failure-free survival (FFS) outcomes were 67% and 49%, respectively. At 5 years, fBT was associated with a 17% cumulative incidence of local failure (LF) outside the GTV (vs. 7.8% ibBT, p=0.14), while LF within the GTV occurred in 13% (vs. 16% ibBT, p=0.81). Predictors of LF outside fBT volumes included pre-salvage PSA>7 ng/mL (p=0.03) and interval since RT less than 5 years (p=0.04). No attributable grade 3 events occurred, and ibBT was associated with a higher rate of grade 2 toxicity (p<0.001), and trend towards a larger reduction in QoL sexual domain score (p=0.07), compared to fBT. Conclusion: A tumor-targeted HDR-BT salvage approach achieved favorable cancer control outcomes. While a fBT was associated with less toxicity, it may be best suited to a subgroup with lower PSA at later recurrence. Tumor targeted dose escalation may be warranted.